Examining Participatory Leadership, Incentives, Loyalty, and Employee Performance: Menganalisis Dampak Kepemimpinan Partisipatif, Insentif, dan Loyalitas terhadap Kinerja Karyawan: Bukti dari Analisis Kuantitatif - Angga Putra; Lilik Indayani (Academia Open, 2022)
This study aimed to examine the influence of participatory leadership style, incentives, and loyalty on employee performance within the marketing department of a retail company in Sidoarjo, Indonesia. Employing a quantitative approach, the study involved 56 employees as respondents. Multiple linear regression analysis was conducted, and hypothesis testing was performed using simultaneous tests, partial tests, multiple correlation coefficient tests, and coefficient tests, facilitated by the SPSS program. The findings revealed that participatory leadership style, incentives, and loyalty collectively had a significant impact on employee performance. Additionally, partial effects of participatory leadership style, incentives, and loyalty were found to significantly influence employee performance. These results emphasize the importance of fostering participatory leadership, providing appropriate incentives, and nurturing employee loyalty to enhance performance within organizations. The implications of these findings for practitioners and researchers are discussed, highlighting the need for effective leadership and incentive systems to optimize employee performance. Highlights: The study examines the impact of participatory leadership, incentives, and loyalty on employee performance. The findings demonstrate the significant influence of participatory leadership, incentives, and loyalty on employee performance. Effective leadership, appropriate incentives, and fostering loyalty are essential for optimizing employee performance. Keywords: Participatory leadership, Incentives, Loyalty, Employee performance, Quantitative analysis